DETERMINAN TIMLINESS OF FINANCIAL REPORTING (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI) - Rahman, Kristanti; Anggraeni, Rahayu (JURNAL EKONOMI, 2021)
This research aimed to analysis the factors Influencing Timeliness of Delivery Financial Reporting. Variables that are used in this study are the profitability, liquidity, and audit opinion. The data that is used in this study was manufactur company sub-sectors of food and beverages listed in Indonesia Stock Exchange. This period of this study was 6 years, started from 2015 until 2020 for was manufactur company sub-sectors of food and beverages listed in Indonesia Stock Exchange. The sampel was selected by means of the purposive sampling technique. The type of data used is secondary data and the total sample used in this study was 60 companies (10 companies x 6 years of observations) that have been selected based on criteria that have been determined. Methods of data analysis used is logistic regression analysis. The result of this study showed that profitability and audit opinion significant factors influencing timeliness of delivery financial reporting. While the liquidity does not factors Influencing Timeliness of Delivery Financial Reporting. Further research is recommended that can expand the research sample, add variables, and extend the period of study. Keywords : Profitability, Liquidity, Audit Opinion and Timeliness